Moral judgment reloaded: a moral dilemma validation study - Christensen, Julia F.; Flexas, Albert; Calabrese, Margareta; Gut, Nadine K.; Gomila, Antoni (Frontiers in Psychology, 2014)
We propose a revised set of moral dilemmas for studies on moral judgment. We selected a total of 46 moral dilemmas available in the literature and fine-tuned them in terms of four conceptual factors (Personal Force, Benefit Recipient, Evitability and Intention) and methodological aspects of the dilemma formulation (word count, expression style, question formats) that have been shown to influence moral judgment. Second, we obtained normative codings of arousal and valence for each dilemma showing that emotional arousal in response to moral dilemmas depends crucially on the factors Personal Force, Benefit Recipient, and Intentionality. Third, we validated the dilemma set confirming that people's moral judgment is sensitive to all four conceptual factors, and to their interactions. Results are discussed in the context of this field of research, outlining also the relevance of our RT effects for the Dual Process account of moral judgment. Finally, we suggest tentative theoretical avenues for future testing, particularly stressing the importance of the factor Intentionality in moral judgment. Additionally, due to the importance of cross-cultural studies in the quest for universals in human moral cognition, we provide the new set dilemmas in six languages (English, French, German, Spanish, Catalan and Danish). The norming values provided here refer to the Spanish dilemma set.